2023
DOI: 10.1093/plphys/kiad349
|View full text |Cite
|
Sign up to set email alerts
|

Combined heat and water stress leads to local xylem failure and tissue damage in pyrethrum flowers

Abstract: Flowers are critical for angiosperm reproduction and the production of food, fibre and pharmaceuticals, yet for unknown reasons they appear particularly sensitive to combined heat and drought stress. A possible explanation for this may be the co-occurrence of leaky cuticles in flower petals and a vascular system that has a low capacity to supply water and is prone to failure under water stress. These characteristics may render reproductive structures more susceptible than leaves to run-away cavitation – an unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
2
2
1
Order By: Relevance
“…Thus, given that the cuticle represents the major hydrophobic barrier against residual water loss (Duursma et al, 2019), and considering that the relative investment in cuticle is positively associated with TMA (John et al, 2017; Onoda et al, 2012), we expected that, due to their lower construction cost, flowers would be leakier to water vapor than leaves. Contrary to our hypothesis, and to the findings of other studies (Bourbia et al, 2020; Carins‐Murphy et al, 2023; Cheng et al, 2021; Roddy, 2023), a clear pattern in the variation of g flower and g leaf‐res within species was not observed (Figure ), which thus resulted in the lack of significant differences in g min between organs (Figure 2c). A possible explanation for these unexpected results may involve the different sources of water leaks integrated by the residual conductance (Duursma et al, 2019; Machado et al, 2020), and their differential contribution to g flower and g leaf‐res .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Thus, given that the cuticle represents the major hydrophobic barrier against residual water loss (Duursma et al, 2019), and considering that the relative investment in cuticle is positively associated with TMA (John et al, 2017; Onoda et al, 2012), we expected that, due to their lower construction cost, flowers would be leakier to water vapor than leaves. Contrary to our hypothesis, and to the findings of other studies (Bourbia et al, 2020; Carins‐Murphy et al, 2023; Cheng et al, 2021; Roddy, 2023), a clear pattern in the variation of g flower and g leaf‐res within species was not observed (Figure ), which thus resulted in the lack of significant differences in g min between organs (Figure 2c). A possible explanation for these unexpected results may involve the different sources of water leaks integrated by the residual conductance (Duursma et al, 2019; Machado et al, 2020), and their differential contribution to g flower and g leaf‐res .…”
Section: Discussioncontrasting
confidence: 99%
“…Despite floral capacitance effectively buffering Ψ flower , a combination of low TSM and LSM make floral organs more vulnerable to turgor loss during hotter‐drought. In line with our findings, a recent study showed that combined heat and drought stresses dramatically increased the likelihood of flower mortality in a perennial crop species (Carins‐Murphy et al, 2023). Importantly, in addition to impairments to reproductive success, increases in air temperature can also compromise overall plant survival under drought conditions, especially for those species with lower flower T p .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations